Narrative Technique In Salman Rushdie's Midnight's Children: Exploring Narrative Techniques and Indian Influences in Salman Rushdie's Midnight's Children (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Salman Rushdie is undoubtly one of the most famous novelists in presenttime. His second novel Midnight's Children received greater critical acclaimand made Rushdie a famous literary figure in English speaking world. The novelwon for him Booker of Bookers prize in 1993. In the novel Rushdie introduces aninnovator narrative technique which is different from the contemporary writers.He uses the first person narrative through Saleem Sinai, the protagonist of thenovel. Rushdie also makes good use of the device of Magic Realism in Midnight'sChildren. Further Rushdie's use of cinematic elements can clearly be seen inthe novel. All this shows Bombay Cinema's influence on Rushdie and Rushdie'suse of Indianized English is his biggest achievement. His use of Indian worldlike ekdum, angrez, firangee etc. give Indian flavor to the novel. Above all,Rushdie can be considered the master of narrative techniques at present time.